Evaluasi Etika Profesi Polisi Dalam Pelayanan Masyarakat Dan Penegakan Hukum : Studi Kasus : Pol Sub Sektor Meranti, Desa Meranti, Kec. Meranti, Kab. Asahan - Sri Nila Sari, Andri Nurwandri, Ade Ilham, Fikri Ibnu Syuhada, Inda Lestari, (CV. PUSDIKRA MITRA JAYA, 2024)
Community service and law enforcement are among the professions required by the police. In evaluating services and law enforcement for the community, the police have a very important role in this field. One of them is that in serving the community, the police must be friendly, caring, polite and polite, and can provide solutions to the community so that the community can experience optimal service. Meanwhile, in law enforcement, apart from serving public complaints, the police also enforce the law. In enforcing this law, the police are required to act fairly, firmly, with authority, and with integrity towards the profession that is their duty. Therefore, in carrying out all these duties, the police also need ethics so that their main goals duties, and functions run well. This research aims to ensure that the professional ethics of the Republic of Indonesia police, in carrying out community service and law enforcement, will become a benchmark for becoming a police officer who can be trusted by all people in Indonesia. Thus creating a safer, fairer, and more dignified society.